(untitled) (Journal of the College of Basic Education, 2023)
The population of some climate elements and relative moisture and winds at the Kut Judiciary Center is important in determining the features of urban formation, a study of temperatures is one of the most important climatic elements that have a direct impact in The life of man and all its activities and heated temperatures and reduce relative humidity and reduce the speed of wind whenever we travel from outside the city because of the frequent human and cars and a large strain part as well as many buildings The contrast in climate elements between separation, indefinition and other area.